Exploration of the Association Between Professional Interactions and Emotional Distress of Intensive Care Unit Nursing Personnel - Kalafati, Maria; Papathanassoglou, Elizabeth; Karanikola, Maria (My University, 2012)
Several studies provide evidence for the association between the quality of collaboration among intensive care unit (ICU) professionals and patients' outcomes, as well as nurses' moral distress and professional satisfaction. However, potential associations between collaboration and nurses' mental health indices have not been explored. The aim of this descriptive correlational study was to investigate the degree of satisfaction from interaction among ICU nursing personnel, as well as between ICU nursing personnel and physicians, and potential associations with ICU nursing personnel's anxiety symptoms. The sample consisted of ICU nursing personnel from 11 adult general hospitals in Greece (n = 229). Hamilton's Anxiety scale was applied for the quantitative assessment of anxiety symptoms and Stamps' Index of Work Satisfaction for the appraisal of nursing personnel's satisfaction from professional interactions. Demographic, vocational, and educational data were also recorded. Descriptive statistics were explored, and group comparisons, correlation, and regression analysis were used. The average satisfaction score from interaction among nursing personnel was moderate to high (5.3 [SD, 1.0]) and from nurse-to-physician interaction was moderate (4.0 [SD, 1.4]) (scale range, 1-7). The score of satisfaction from nurse-to-physician interaction was negatively mildly correlated with participants' (a) total anxiety score ( = ?0.160, P = .001), (b) tension ( = ?0.125, P = .015), and (c) depressive symptoms ( = ?0.148, P = .005). Weak negative correlations were detected between satisfaction from interaction among nursing personnel and participants' (a) total anxiety state ( = ?0.139, P = .003), (b) tension ( = ?0.137, P = .008), and (c) sleep disturbances ( = ? 0.150, P = .003). Overall, female respondents had higher levels of anxiety symptoms than male respondents (Mann-Whitney U, P = .007). Satisfaction from professional interaction was not a strong predictor of anxiety symptoms among ICU nursing personnel (R2 = 0.046, ?0.15). Nursing personnel in Greek ICUs seem to be satisfied with the quality of relationships among them, as well as with physicians. Despite that anxiety symptoms associate with the degree of satisfaction from professional interaction, the latter may not be a significant indicator of ICU nurses' well-being. Further qualitative research is needed to identify mediating factors
Keywords: Critical care nursing; Intensive care units; Intensive care nursing; Greece; Job satisfaction; Sex differences; Stress (Psychology)